2022
DOI: 10.1155/2022/3495966
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Investigation on the Inhibitory Effect of Methotrexate on Rheumatoid Synovitis via the TLR4‐NF‐κB Pathway in a Rat Model

Abstract: Rheumatoid arthritis (RA) is a rheumatoid immune system disease characterized by joint inflammation, resulting in synovial hyperplasia, articular cartilage damage or distortion, and extra-articular involvement. The morbidity is higher and the treatments are not effective in clinical, and also no unified to the pathogenesis of such diseases. The aim of this paper is to establish a rat model of rheumatoid synovitis and observe the inhibitory effect of methotrexate on this disease. A total of 100 SD rats are sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies reported elevated levels of TRAF6 and IRAK, downstream targets of the TLR4/MYD88 pathway, in fibroblast-like synoviocytes, suggesting their role in rheumatogenic processes ( Zhang et al, 2022 ). In line with these findings, we noticed an increase in TRAF6 and IRAK expression in rats treated with FCA, compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies reported elevated levels of TRAF6 and IRAK, downstream targets of the TLR4/MYD88 pathway, in fibroblast-like synoviocytes, suggesting their role in rheumatogenic processes ( Zhang et al, 2022 ). In line with these findings, we noticed an increase in TRAF6 and IRAK expression in rats treated with FCA, compared to the control group.…”
Section: Discussionmentioning
confidence: 98%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%